If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + -7 = -7x + 13 Reorder the terms: -7 + -5x = -7x + 13 Reorder the terms: -7 + -5x = 13 + -7x Solving -7 + -5x = 13 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -7 + -5x + 7x = 13 + -7x + 7x Combine like terms: -5x + 7x = 2x -7 + 2x = 13 + -7x + 7x Combine like terms: -7x + 7x = 0 -7 + 2x = 13 + 0 -7 + 2x = 13 Add '7' to each side of the equation. -7 + 7 + 2x = 13 + 7 Combine like terms: -7 + 7 = 0 0 + 2x = 13 + 7 2x = 13 + 7 Combine like terms: 13 + 7 = 20 2x = 20 Divide each side by '2'. x = 10 Simplifying x = 10
| 10y-3=7 | | -8x-11x=133 | | q-5=35 | | 4+4m=-m-1 | | 12x^2=6-x | | -5.5x=110.0 | | 3=-3x | | (4x^4+2n)-(8x^4+14n)= | | -5.5=110.0 | | -(3x-2)=3x | | 5z^6-(-3z^6-3v)= | | 6x+4y+xy+24= | | (-2w^4+11v)-(-15w^4)= | | -23+x=x+15 | | 3+2(2x-3)=1 | | 8x^9-(6x^9-7)= | | Y-6(y-4)=(-8y+15)-5 | | (-9b^9-11n)-(6b^9-7n)= | | 2x-12=6x-2 | | 15x^2=16x+7 | | (8a^4+5d)-(3a^4+3d)= | | (-14z^2+4)-13z^2= | | B=yt+y | | (-6y^5-5)-13y^5= | | -2=4y-7+5y | | 3-4(x+3)-5=3+2(4-2x)-16 | | 8x^2+6x+7=0 | | 3y-2+y+42=8y+40-6y | | .5(3x-6)=3(x-2) | | 7=5t+6+5t | | n^2-3n-1=0 | | 10y^8-(4y^8+13)= |